Effect of Direct Recycling Hot Press Forging Parameters on Mechanical Properties and Surface Integrity of AA7075 Aluminum Alloys - Nasha Emieza Ruhaizat; Nur Kamilah Yusuf; Mohd Amri Lajis; Sami Al-Alimi; Shazarel Shamsudin; Ikhwan Shah Tisadi Tukiat; Wenbin Zhou (Metals, 2022)
The current practice in aluminum recycling plants is to change the waste into molten metal through the conventional recycling (CR) manufacturing process. However, the CR technique is so energy-intensive that it also poses an indirect threat to the environment. This paper presents a study on meltless direct recycling hot press forging (DR-HPF) as an alternative sustainable approach that has fewer steps with low energy consumption, as well as preventing the generation of new waste. A laboratory experiment was conducted to study the mechanical properties and surface integrity of AA7075 aluminum alloy by employing a hot press forging (HPF) process under different temperatures (380, 430, and 480 °C) and holding times (0, 60, and 120 min). It was found that as the parameter increased, there was a positive increase in ultimate tensile strength (UTS), elongation to failure (ETF), density, and microhardness. The recycled chips exhibit the best mechanical properties at the highest parameters (480 °C and 120 min), whereas the UTS = 245.62 MPa and ETF = 6.91%, while surface integrity shows that the calculated microhardness and density are 69.02 HV and 2.795 g/cm3, respectively. The UTS result shows that the highest parameters of 480 °C and 120 min are comparable with the Aerospace Specification Metals (ASM) Aluminum AA7075-O standard. This study is a guide for machinists and the manufacturing industry to increase industry sustainability, to preserve the earth for future generations.